Mathematical modeling of some social processes using game-theoretic approaches and making managerial decisions based on them - К. Е. Krasnikov (Российский технологический журнал)
In this article, using game-theoretic approaches, the human community is modeled as a dynamic system, and the influence of such ethical norms of behavior as egoism and altruism, morality (on the example of the Kant imperative or the Golden Rule of Morality) on the state of this system is investigated, as well as the question of determining the effectiveness of the community depending on the prevailing worldview of its representatives. Using the example of a game model of social choice between two norms of behavior – one generally accepted, but outdated, and another, new, not yet widespread, but more advanced and progressive – it is shown that communities, among whose representatives a predominantly egoistic worldview prevails, are less likely to innovate and abandon outdated norms of behavior. Conversely, those communities whose representatives share basic ethical principles are more confident and quickly moving to advanced and progressive norms. In conclusion, the paper examines the question of what advantages a society acquires in which purposeful educational and educational activities are conducted, designed to increase the level of morality and morality among its representatives. The results obtained can be used, firstly, as an integral part of the course on the mathematical base of ethics, which could perform the functions of educational work in higher and secondary educational institutions; and, secondly, for the purposes of evaluating the effectiveness of educational work and state planning in this area.